How Does Poverty Differ Among Refugees? Taking a Gender Lens to the Data on Syrian Refugees in Jordan - Hanmer, Lucia; Arango, Diana J.; Rubiano, Eliana; Santamaria, Julieth; Viollaz, Mariana (World Bank, Washington, DC, 2018)
Data collected for refugee registration and to target humanitarian assistance include information about household composition and demographics that can be used to identify gender-based vulnerabilities. This paper combines the microdata collected by United Nations High Commissioner for Refugees to register refugees with data from its Home Visit surveys to analyze income poverty rates among refugees with a gender lens. It finds distinguishing between different types of male and female principal applicant (PA) households is important in the setting of Syrian refugees in Jordan. Poverty rates for couples with children do not differ by gender of the PA but for other household types poverty rates are higher for those with female PAs. Households formed because of the unpredictable dynamics of forced displacement, such as sibling households, unaccompanied children, and single caregivers, are extremely vulnerable, especially if the principal applicant is a woman or a girl.